Basics Statistics Critical Thinking Test : Reliability and Validity Issues - Mohd Afifi Baharudin Setambah; Nor'ain Mohd Tajudin; Mazlini Adnan (Didaktik Matematika, 2018)
This study aims to examine the validity and reliability of Statistics Critical Thinking Test (SCTT) for Institute of Teachers Education students using the Content Validity Index (CVI). The assessment was conducted through the evaluation by 3 experts and 30 students selected via purposive sampling. The instrument involved 30 items with two main constructs such as evaluation and interpretation. The result of analysis, CVI is 0.99. This instrument also has 0.71 of reliability value. The results of the study prove that the instrument has good validity and reliability. SCTT has a great potential to be promoted as a good measurement instrument. This instrument is recommended to be used to measure critical thinking level for others college students.